Why Trust Science? - Oreskes, Naomi (Princeton : Princeton University Press, 2021)
Are doctors right when they tell us vaccines are safe? Should we take climate experts at their word when they warn us about the perils of global warming? Why should we trust science when so many of our political leaders don't? Naomi Oreskes offers a bold and compelling defense of science, revealing why the social character of scientific knowledge is its greatest strength--and the greatest reason we can trust it. Tracing the history and philosophy of science from the late nineteenth century to today, this timely and provocative book features a new preface by Oreskes and critical responses by climate experts Ottmar Edenhofer and Martin Kowarsch, political scientist Jon Krosnick, philosopher of science Marc Lange, and science historian Susan Lindee, as well as a foreword by political theorist Stephen Macedo. --
Introduction / Stephen Macedo -- Why trust science? : perspectives from the history and philosophy of science -- Science awry -- Coda: Values in science -- Comments. The epistemology of frozen peas : innocence, violence, and everyday trust in twentieth-century science / Susan Lindee -- What would reasons for trusting science be? / Marc Lange -- Pascal's wager reframed : Toward trustworthy climate policy assessments for risk societies / Ottmar Edenhofer and Martin Kowarsch -- Comments on the present and future of science, inspired by Naomi Oreskes / Jon A. Krosnick -- Response. Reply -- Afterword.
With a new preface by the author.
Includes bibliographical references (pages 297-334) and index.
Keywords: Science -- Social aspects; Science -- Philosophy; Sciences -- Aspect social; Science -- Social aspects; Science -- Philosophy